Origin and spread of leprosy in Suriname. A historical and biomedical study - Faber, William R.; Sewpersad, Karin; Menke, Henk; Avanzi, Charlotte; Geluk, Annemieke; Verhard, Els M.; Tió Coma, Maria; Chan, Mike; Pieters, Toine (Frontiers in Tropical Diseases, 2023)
The new world was considered free of leprosy before the arrival of Europeans. In Suriname, historical migration routes suggest that leprosy could have been introduced from West Africa by the slave trade, from Asia by indentured workers, from Europe by the colonizers, and more recently by Brazilian gold miners. Previous molecular studies on environmental and ancient samples suggested a high variability of the strains circulating in the country, possibly resulting from the various migration waves. However, a current overview of such diversity in humans still needs to be explored.The origin and spread of leprosy in Suriname are investigated from a historical point of view and by strain genotyping of Mycobacterium leprae from skin biopsies of 26 patients with multibacillary leprosy using PCR-genotyping and whole-genome sequencing. Moreover, molecular signs of resistance to the commonly used anti-leprosy drugs i.e. dapsone, rifampicin and ofloxacin, were investigated.Molecular detection was positive for M. leprae in 25 out of 26 patient samples, while M. lepromatosis was not found in any of the samples. The predominant M. leprae strain in our sample set is genotype 4P (n=8) followed by genotype 1D-2 (n=3), 4N (n=2), and 4O/P (n=1). Genotypes 4P, 4N, 4O/P are predominant in West Africa and Brazil, and could have been introduced in Suriname by the slave trade from West Africa, and more recently by gold miners from Brazil. The presence of the Asian strains 1D-2 probably reflects an introduction by contract workers from India, China and Indonesia during the late 19th and early 20th century after the abolition of slavery. There is currently no definite evidence for the occurrence of the European strain 3 in the 26 patients. Geoplotting reflects internal migration, and also shows that most patients live in and around Paramaribo. A biopsy of one patient harbored two M. leprae genotypes, 1D-2 and 4P, suggesting co-infection. A mutation in the dapsone resistance determining region of folP1 was detected in two out of 13 strains for which molecular drug susceptibility was obtained, suggesting the circulation of dapsone resistant strains.